JEMBATAN APUNG GUNUNG JATI DENGAN PONDASI PONTOON TANPA MENGGUNAKAN TIANG PENYANGGA SEBAGAI SOLUSI TRANSPORTASI DARAT PENGHUBUNG JAWA-SUMATERA - Putra, Arief Wiratama; Ikawidjaja, Meutia; Anjasmara, Brian Pradipta; Ichsandyarrachman, Ardhi; Dewi, I Dewa Ayu Dwika Puspita (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Indonesia as an archipelagic country has an area of 1,910,931.32 km2 with a population density reached 237.36 million in 2010, with thus Indonesia has great potential to enhance the natural resources, and human resources that can not be separated from life on the islands of Sumatra and Java. Java and Sumatra is an island that has the potential to promote development in the country. Marine transportation is used as a link the two islands has many shortcomings, such as not able to serve the needs of people who want to cross the island of Java and Sumatra, well, because it is hampered fleet size is limited, and expensive ferry freight rate. This is a barrier for people crossing, due to the fact that private vehicles and cargo that want to cross had to queue up for hours to wait penyebarangan. See the underwater topography of Sunda strait vulnerable plate movement and saplings Krakatoa makes conventional bridge construction is a solution that is not quite right. Therefore, the construction of the floating bridge is the most appropriate solution as a means of land transportation connecting Java and Sumatra. Floating bridge pontoon which we propose to use as a replacement solution using a conventional bridge foundations are stuck at the bottom of the sea surface, it would disrupt the ecology of the sea bottom and the underwater topography is possible will often occur and transfersal longitudinal vibration caused by magma activity under the sea. With the construction of pontoon bridges can reduce the risks and obstacles that occur during the development progresses. By using the laws of physics Archimides building construction and design of a concept which has been updated from existing bridge in Washington DC / Seattle, Gunung Jati bridge is believed to be able to address the challenges that exist in the Sunda Strait. The problem of water flow down will not impact directly on the foundation materials floating pontoon bridge is made more profitable than conventional bridges using pole foundation rooted on the seabed.